2013
DOI: 10.1371/journal.pone.0054719
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT/TNFSR14 Can Regulate Hepatic Lipase Expression by Hepatocytes Independent of T Cells and Kupffer Cells

Abstract: LIGHT/TNFSF14 is a costimulatory molecule expressed on activated T cells for activation and maintenance of T cell homeostasis. LIGHT over expressed in T cells also down regulates hepatic lipase levels in mice through lymphotoxin beta receptor (LTβR) signaling. It is unclear whether LIGHT regulates hepatic lipase directly by interacting with LTβR expressing cells in the liver or indirectly by activation of T cells, and whether Kupffer cells, a major cell populations in the liver that expresses the LTβR, are req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Moreover, Light deficiency decreased insulin resistance in HFHCD-fed WT mice, suggesting that LIGHT could interfere with insulin sensitivity, as has been shown for other cytokines such as TNF-α [24]. LIGHT exerts important effects on circulating lipid levels by modulating hepatocyte gene expression and hepatic T lymphocytes [23,25]. However Light deficiency did not modify circulating lipid levels in WT mice.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, Light deficiency decreased insulin resistance in HFHCD-fed WT mice, suggesting that LIGHT could interfere with insulin sensitivity, as has been shown for other cytokines such as TNF-α [24]. LIGHT exerts important effects on circulating lipid levels by modulating hepatocyte gene expression and hepatic T lymphocytes [23,25]. However Light deficiency did not modify circulating lipid levels in WT mice.…”
Section: Discussionmentioning
confidence: 79%
“…Since the activity of HL is known to be inversely correlated with the plasma HDL levels [2] the study of factors which regulate HL activity is important in understanding the regulation of HDL metabolism. Whereas the regulation of HL transcription, synthesis and secretion from the liver have been well studied [1,68], the physiological factors that regulate its activity in the plasma compartment are not well understood. Furthermore, while it is known that HL acts preferentially on HDL compared to VLDL and LDL [4], the reason for this specificity is unknown, since it does not require an apoprotein cofactor for its activity.…”
Section: Introductionmentioning
confidence: 99%
“…We have studied LIGHT expressed as a transgene in T cells and shown that it substantially down regulates the expression of hepatic lipase, a plasma enzyme involved in HDL metabolism 42 . We have also shown that the expression of LIGHT primarily by hepatocytes in mice using an adenovirus also reduces hepatic lipase expression independent of T cells 43 . In the presence of LIGHT overexpressing T cells in WTD fed Ldlr−/− mice a novel large HDL-like lipoprotein, HDL1, which is almost devoid of apoA-I, but is rich in apoE appears in the plasma.…”
Section: T Cell Costimulatory/coinhibitory Moleculesmentioning
confidence: 69%